The Resistance of Palembang’s Local Religious Elites to Dutch East Indies Islamic Politics in the 20th Century - Nur Fitriyana; Titik Pudjiastuti; Izomiddin Izomiddin (IAIN Ponorogo, 2023)
The 19th century was the peak of the mission era and the beginning of the 20th century was the period of independence of the Protestant Church by inviting various missionary organizations from Europe to carry out their missions in the Dutch East Indies. This was a major threat to Muslims, including Palembang Malay Muslims. This article seeks to complement existing research with the aim of knowing the resistance factors of local elites in the Palembang Malay community. This study uses a socio-historical approach by making use of James C. Scoot’s resistance theory. Scoot’s theory of resistance. This study concludes that the resistance of local elites in Palembang Malay society is caused by the central role of local religious elites in preaching and teaching the Muslim community in Palembang to remote areas. The elites a r e in the category of free ulama. Figures such as Abdullah Munsyi and the Samaniyah tarekat teachers who made various efforts to save Muslims from Islamic politics run by the Dutch East Indies. Efforts were made such as the construction of various places that served as centers of Islamic studies such as langgar, mosques, and madrasas.